Safety Analysis Using Lebesgue Strain Measure of Thick-Walled Cylinder for Functionally Graded Material under Internal and External Pressure - A. K. Aggarwal; Richa Sharma; Sanjeev Sharma (The Scientific World Journal)
Safety analysis has been done for thick-walled circular cylinder under internal and external pressure using transition theory which is based on the concept of generalized principal Lebesgue strain measure. Results have been analyzed theoretically and discussed numerically. From the analysis, it can be concluded that circular cylinder made of functionally graded material is on the safer side of the design as compared to homogeneous cylinder with internal and external pressure, which leads to the idea of “stress saving” that minimizes the possibility of fracture of cylinder.